Quadriceps Avoidance After Total Knee Arthroplasty: Descriptive Study - Muhammad Nauman Jamal, Ans Hanif, Sameen Saeed, Sidra Shabbir, Ishrat Fatima, Shah Salman, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Quadriceps avoidance is a reflex deficit disorder of quadriceps activation after total knee arthroplasty (TKA) that can lead to abnormal gait kinematics. It is patient apprehension due to pain, to prevent quadriceps activation that induces deforming forces at the knee joint. Aim: To describe the frequency of ‘quadriceps avoidance’ among patients after total knee arthroplasty. Study Design: Descriptive case series. Methodology: The study sample size comprised of 55 post-TKA patients (Male: 16; Female: 39), who were the ages of 40-80 years. Participants were recruited who had undergone unilateral total knee replacement and attended an outpatient physiotherapy clinic of Ghurki trust teaching hospital and Surgimed hospital Lahore. Participants were undergone ‘quadriceps avoidance gait’ testing at approximately 02 weeks and 01 month postoperatively by using a diagnostic observational questionnaire, designed according to the observational gait analysis. Data was evaluated by using SPSS version 23. All qualitative data was presented in frequency form and quantitative data was in the form of mean±SD. Results: Mean age of patients was 58.98 with range minimum of 40 years to a maximum of 80 years. Out of a sample size of 55, 25 (45.5%) patients were diagnosed with quadriceps avoidance after TKA, 11(20%) were male patients out of 16 and 14 (25.5%) were female patients out of 39 which showed ‘stiff knee gait’ pattern. Conclusion: It was concluded that quadriceps avoidance after total knee arthroplasty was one of major complication of abnormal gait pattern which can lead to knee joint deformities if left uncorrected. Keywords: Total knee arthroplasty, Quadriceps avoidance, Gait kinematics, Gait kinetic